Empowerment of Women through Economic Independency in Patna Metropolitan Cit - Pandey, Purnima; Rai, Gayatri (National Geographical Journal of India, 2022)
Women empowerment is an essential tool to bring about changes in their socio-economic condition. Empowerment of women needs to begin with their participation in different spheres of life. Education is a great determinant in this regard. To achieve empowerment, women have to be educated about their rights and privileges in a modern society. It is the education that can bring about awareness in them related to their social status, injustice and differentiation meted out to them. In Patna metropolitan city, women plays a significant role not only in economic development but also in social, political, religious aspects etc.The present study is undertaken to analyze the importance of women's in decision making in regard to freedom of movement, family matters, purchasing home assets and family planning etc. This study examines the factors (particularly the independent variables) that might affect women's decision making power at the household level. In the present work both primary and secondary data have been used. The study indicates that status of women is not good, as they are depend on men's income and their occupational status is not equal to men. Therefore, they cannot take decision in the economic matters at family level.